Incentives in Swedish commercial real estate companies: the property manager function. Issue 2 (18th April 2017) - Palm, Peter
Abstract : Purpose: The purpose of this paper is to identify factors on the property management level for analysing incentives for an effective property management with a focus on organising it in-house. Design/methodology/approach: This research is based on an interview study of 11 firm representatives from the Swedish commercial real estate sector with in-house property management. Findings: The study concludes that the property management organisation in the in-house setting is governed in an informal way, with a large portion of "freedom with responsibilities" setup instead of regulations. Research limitations/implications: The research in this paper is limited to the Swedish commercial real estate sector. Practical implications: The insights into the paper regarding how decision makers create incentives for the property management organisation can provide inspiration to design incentives for effort. Originality/value: It provides an insight regarding how the commercial real estate industry prioritises different work tasks and how incentives are created to enable effort.